Numerical simulation and industrial practice of inclusion removal from molten steel by gas bottom-blowing in continuous casting tundish - Meijie Z.; Huazhi G.; Ao H.; Hongxi Z.; Chengji D. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Gas blowing at the bottom of tundish is an efficient metallurgy technique in clean steelmaking. In this paper, the removal of small size inclusions in the gas bottom-blowing tundish was studied by numerical simulation and industrial practice. The residence time distribution (RTD) of molten steel in the tundish was calculated by mathematical modeling. The content of small size inclusions in the slab was analyzed using a oxygen probing and metallographic images. The results show that the molten steel characteristics obviously change when applied gas bottom-blowing, the average residence time of molten steel in the tundish prolongs more than 100s and the dead volume fraction decreases about 5%. Therefore, the removal efficiency of small size inclusions greatly increases because of bubbles attachment and long moving path. Industrial experiment results show that the average inclusions content of less than 20μm decreases more than 24%, the average overall oxygen content decreases about 15% when controlling the reasonable blowing parameters.